The Influence of Self-Efficacy and Motivation to Enter the Workforce on Job Readiness: A Study of Fourth-Year Diploma Students in Hospitality Management at State University of Padang (Class of 2021) - Muhammad Hafizd; Azmen Kahar (Journal of Multidimensional Management, 2025)
This study examines the influence of self-efficacy and motivation to enter the workforce on the job readiness of final-year diploma students majoring in Hospitality Management at Padang State University, Indonesia. Adopting a quantitative and causal-associative approach, data were collected through structured questionnaires from 60 students and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The measurement model demonstrated strong reliability and validity, with all constructs satisfying convergent and discriminant validity criteria. The structural model results indicate that self-efficacy (β = 0.266, p < 0.01) and motivation to enter the workforce (β = 0.649, p < 0.001) significantly and positively affect job readiness, with motivation showing a stronger predictive effect. The model accounted for 58.1% of the variance in job readiness, confirming substantial explanatory power. These findings highlight the importance of psychological and motivational factors in shaping vocational students’ employability and suggest the need for educational programs to foster both self-efficacy and career motivation as part of student development strategies.